Living Mantra Mantra, Deity, and Visionary Experience Today - Rao, Mani.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Living Mantra is an anthropology of mantra-experience among Hindu-tantric practitioners. In ancient Indian doctrine and legends, mantras perceived by rishis (seers) invoke deities and have transformative powers. Adopting a methodology that combines scholarship and practice, Mani Rao discovers a continuing tradition of visionaries (rishis/seers) and revelations in south India's Andhra-Telangana. Both deeply researched and replete with fascinating narratives, the book reformulates the poetics of mantra-practice as it probes practical questions. Can one know if a vision is real or imagined? Is vision visual? Are deity-visions mediated by culture? If mantras are effective, what is the role of devotion? Are mantras language? Living Mantra interrogates not only theoretical questions, but also those a practitioner would ask: how does one choose a deity, for example, or what might bind one to a guru? Rao breaks fresh ground in redirecting attention to the moments that precede systematization and canon-formation, showing how authoritative sources are formed.
Part 1: Preparation -- 1. Introduction -- 2. A Mountain of Scholarship -- 3. Crossing Over -- 4. Are there Revelations Today? - Part 2: Fieldwork -- 5. Body-Yantra: Sahasrakshi Meru Temple, Devipuram -- 6. Self-Made: Svayam Siddha Kali Pitham, Guntur -- 7. "I am in Mantra, Mantra is in me": Nachiketa Tapovan, Kodgal -- Part 3 -- 8. Understanding Mantra Again.
Keywords: Ethnology; Religion and sociology; Ethnography; Sociocultural Anthropology; Sociology of Religion